Penyuluhan Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Siswa Sekolah Luar Biasa (SLB-C) Karya Ibu Kota Palembang - Juliyanda, Nugraha; Lestari, Peggy Ayu; Cynthia, Cynthia; Hayati, Thursina Vera; Hidayatullah, Muhammad Dwi; Khaeriyah, Muthia; Fitriani, Novi; Sari, Merry Afriliana; Astari, Dea Widya; Pradisa, Dea; Yuliantari, Devy; Apriliani, Ferenadia; Safithri, Vani; Idris, Haerawati (Universitas Muhammadiyah Tangerang, 2024)
Self-care activities are the ability to improve health by preventing disease and overcoming illness. Intellectually Disabled Children are expected to be able to carry out self-care independently, such as through implementing Clean and Healthy Living Behaviour (CHLB). This activity aims to provide understanding and CHLB skills, through the implementation of hand wash and dispose of waste. The activity method is counselling and practice using posters, power points and educational videos. The activity was held on November 9 2023 at the Karya Ibu Palembang C Special School (SLB-C). The targets of the activity are SLBC students, teachers and parents. The results of the activity showed that students were enthusiastic in participating in the activity. The activities are fully supported by teachers and parents, as can be seen from their presence. Extension activities have been proven to improve students' ability to carry out hand wash and dispose of waste. There are challenges faced in implementing activities, there are some students who lack focus in paying attention during counselling. CHLB for Intellectually Disabled Children is important to be carried out on an ongoing basis, the role of parents and teachers is needed to support the implementation of CHLB for Intellectually Disabled Children